Clients, clients, and more clients create an endless stream of new business with the power of psychology - Kase, Larina (McGraw-Hill, 2012)
Convert relationships into revenue-generating business! With Clients, Clients, and More Clients, you'll learn how to capture the attention of the right connections, build loyal relationships, and influence people to hire you. Larina Kase combines the latest research from the field of psychology with her own background as a marketing psychologist to help you understand exactly how potential clients think-and use this information to close the deal. Discover how to understand the true needs of a client; access underlying emotions through the use of metaphor; alleviate clients' stress or fears; use color and design psychology to optimize your branding; make yourself memorable; use endorsements in the way that really works; package your products and services so people decide to purchase them. Larina Kase, PsyD, MBA, is a cognitive-behavioral psychologist and marketing consultant to service business owners. She publishes the monthly ezine Stand Out! Marketing that Grabs Attention and Gets Results and is the author or coauthor of several business books, including The Confident Leader and The Confident Speaker . Praise for Clients, Clients, and More Clients "If 'who you know' and making a meaningful connection with them is truly part of the success factor in business (and it is), I promise you that Larina Kase's Clients, Clients, and More Clients will have your phone ringing and e-mail box full of people who truly want to do business with you. A savvy, wise, and value-based text allows the reader to learn what few others understand: the Science and Art of Connecting. I've read and reviewed a dozen books on building a solid client base. Most completely miss the target. This book is a handbook to meet, connect with, and build a valuable relationship with just about anyone you want to."--Kevin Hogan, Psy. D., author of The Science of Influence and The Psychology of Persuasion "This is a remarkable, readable, and instantly practical book packed with leading-edge tips on attracting new clients fast. I loved it!"--Dr. Joe Vitale, author of The Attractor Factor "In Clients, Clients, and More Clients, Larina Kase shows you how to find and influence prospects so they'll understand the value of your work and readily do business with you. The research-based strategies in this important and engaging book are worth any businessperson's time, close study, and dedicated application. The book is true to its promises."--Mark Levy, founder of Levy Innovation and author of Accidental Genius: Using Writing to Generate Your Best Ideas, Insight, and Content " Clients, Clients, and More Clients is a must-read for every sales executive, sales manager, and company executive. This is not your typical how-to sales guide, as it digs deep into how to change a losing sales strategy into a winning success. Larina uncovers the psychology behind the sales mentality, and breaks the process down, step-by-step; making it crystal clear the direction you'll need to take to achieve long-term success."--Shawn Jennings Edgington, CIC, CEO, and founder of Granite Insurance Brokers, Cyber Safety Academy Fundraiser, and author of The Parent's Guide to Texting, Facebook and Social Media "Whether you call it the power of psychology or a magnetic personality, the techniques, strategies, and tactics Dr. Larina Kase outlines are exactly what I have used to assist in producing over USD20 million in online sales, tens of thousands of customers, and raving fans throughout the world in the past five years. It all begins with your ability to communicate and build relationships, and this book gives a step-by-step process on how to get people to know, like, and trust you. With that.
Title from title screen. - Includes bibliographical references and index
Keywords: Business networks; Customer relations -- Psychological aspects; Interpersonal relations; Relationship marketing; Réseaux d'affaires; Marketing relationnel; Commerce; Business & Economics; Marketing & Sales